Wpływ egzaminu gimnazjalnego z języka angielskiego na proces nauczania i uczenia się - Ellis, Melanie (Neofilolog, 2019)
Questionnaires were used to gather data from learners in class 3 lower secondary school and their teachers. This information was compared with data obtained a year earlier during a baseline study, with the aim of assessing what effect the new external examination in English had had on the teaching and learning process. It was found that the examination appears to have positively influenced learner motivation and caused teachers to change materials and teaching techniques.